The Effect of Audio-Visual Distraction on Catheterization Pain among School-Age Children - Mohadese Babaie; Azam Shirinabadi Farahani; Manijeh Nourian; Asma Pourhoseingholi; Anahita Masoumpour (Mashhad University of Medical Sciences, 2019)
Background: Catheterization is the most common cause of pain and distress in children, which causes physical and psychological dysfunctions and disrupts the treatment. Therefore, the control of this type of pain should be considered as a priority for nursing care. The audio-visual distraction can be used to reduce the intensity of pain. Aim: The purpose of this study was to determine the effect of audio-visual distraction on catheterization pain among school-age children. Methods: This randomized clinical trial included 64 school-age children assigned into intervention and control group in Qods Hospital during 2016. Oucher face pain intensity scale was utilized to evaluate the intensity level of pain.  Catheterization duration was also recorded in this study. Data were analysed in SPSS software (Version.18) through descriptive statistics, t-test, Mann-Whitney U test, and Spearman correlation analyses. Results: The mean ages of the intervention and control groups were 7.8±1.4 and 7.7±1.6, respectively. The results of the Mann-Whitney U test showed that the mean pain intensity was lower in the intervention group after using the three-dimensional glasses (P=0.01). Spearman correlation test results indicated that there were no significant differences between different ethnicities (P=0.37) and birth ratings (r=-0.061, P-value=0.63) in terms of mean pain intensity.  Implications for Practice: According to the results, the use of distraction methods could  reduce the pain. In addition, they facilitated medical procedures. The role of variables, such as age, gender, and duration of catheterization should be considered in pain intensity.